2010
DOI: 10.1038/gene.2010.45
|View full text |Cite
|
Sign up to set email alerts
|

Mus spretus SEG/Pas mice resist virulent Yersinia pestis, under multigenic control

Abstract: Laboratory mice are well known to be highly susceptible to virulent strains of Yersinia pestis in experimental models of bubonic plague. We have found that Mus spretus-derived SEG/Pas (SEG) mice are exceptionally resistant to virulent CO92 and 6/69 wild type strains. Upon subcutaneous injection of 10 2 colony-forming units (CFU), 90% of females and 68% of males survived, compared with only an 8% survival rate for both male and female C57BL/6 mice. Furthermore, half of the SEG mice survived a challenge of up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…A recent study using fully virulent plague pathogens found that multiple loci were required for mice to survive in a Y. pestis subcutaneous infection model (32)(33)(34) (12), and DBA2/J mice (M. Tencati and R. Tapping, unpublished data). The resistance in BALB/cJ mice has been localized to chromosome 17, whereas at least part of the resistance in 129 mice localizes to chromosome 1.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using fully virulent plague pathogens found that multiple loci were required for mice to survive in a Y. pestis subcutaneous infection model (32)(33)(34) (12), and DBA2/J mice (M. Tencati and R. Tapping, unpublished data). The resistance in BALB/cJ mice has been localized to chromosome 17, whereas at least part of the resistance in 129 mice localizes to chromosome 1.…”
Section: Discussionmentioning
confidence: 99%
“…The SEG/Pas strain of Mus spretus is highly resistant to pigmentation-positive Y. pestis (2). Multiple alleles that contributed to resistance in SEG/Pas mice were discovered (2). The mean times of death of SEG/Pas mice and C57BL/6 mice were similar (2).…”
mentioning
confidence: 68%
“…Plague resistance has also been seen in another mouse species. The SEG/Pas strain of Mus spretus is highly resistant to pigmentation-positive Y. pestis (2). Multiple alleles that contributed to resistance in SEG/Pas mice were discovered (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations